Learning in Communities Interdisciplinary Perspectives on Human Centered Information Technology - Carroll, John M. (Human-Computer Interaction Series, 2009)
Most learning takes place in communities. People continually learn through their participation with others in everyday activities. Such learning is important in contemporary society because formal education cannot prepare people for a world that changes rapidly and continually. We need to live in learning communities. This collection of papers is not the definitive summary of learning in communities. It is assuredly more prolegomena than coda. Learning is increasingly recognized as a critical facet of lifetime activity, one that must become better integrated with all that people do. At the same time, community structures are increasingly recognized as a critical category of social organization - flexible and adaptable, capable of innovation and development, and yet just as strongly nurturing and supportive. The promise of learning in communities lies ahead of us. This set of essays intends to propel us all along that path.